1994
DOI: 10.1016/0735-1097(94)90423-5
|View full text |Cite
|
Sign up to set email alerts
|

Insuline resistance, lipoproteins, body fat and hemostasis in nonobese men with angina and a normal or abnormal coronary angiogram

Abstract: These findings provide new evidence of the central role of insulin resistance and hyperinsulinemia in the development of risk factors associated with coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 41 publications
1
14
0
3
Order By: Relevance
“…This ®nding is in keeping with some coronary angiographic studies in which fasting insulin was measured. 11,12 The comparable degree of coronary damage we found in smokers and non-smokers, as well as in drinkers and non-drinkers, independently of the amount of # Selected as being signi®cantly correlated with coronary score in the group-related Pearson analysis. NI not included in the model because their P-value was b 0.1 in the group-related Pearson analysis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This ®nding is in keeping with some coronary angiographic studies in which fasting insulin was measured. 11,12 The comparable degree of coronary damage we found in smokers and non-smokers, as well as in drinkers and non-drinkers, independently of the amount of # Selected as being signi®cantly correlated with coronary score in the group-related Pearson analysis. NI not included in the model because their P-value was b 0.1 in the group-related Pearson analysis.…”
Section: Discussionmentioning
confidence: 71%
“…3,4 In recent years, the correlation of CAD with body fat was also studied directly using coronary angiography. 5 ± 15 In the majority of these studies CAD was found to be signi®cantly correlated with abdominal fat distribution, which was evaluated by waist-to-hip ratio (WHR) or waist-to-thigh ratio (WTR), dual energy X-ray absorptiometry (DEXA) 12 and by computer tomography (CT) scanning at L4 level. 10 To a variable extent this correlation was also found with age, sex, serum cholesterol, triglyceride, LDL-cholesterol, or systolic blood pressure, exceptionally with body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…Male non-diabetic CHD patients were assigned to 3 CHD groups according to their GS (tertile values were used as cutoff points) and according to the number of diseased coronary arteries. Ley et al showed that even patients with angina pectoris with normal coronary arteriograms had a 28% lower insulin sensitivity than normal controls, 33 and Chauhan et al showed that patients with syndrome X with normal coronary arteriograms exhibited hyperinsulinemia. 34 In our study, hyperinsulinemia, as reflected by increased fasting levels of insulin and insulin response during the OGTT, and IR, as measured by the HOMA model, were significantly and linearly associated with the severity of coronary atherosclerosis as measured by GS and by the number of diseased coronary arteries (Tables 5,6).…”
Section: Discussionmentioning
confidence: 99%
“…A síndrome de resistência à insulina, mesmo excluindo-se hipertensos, parece, também, ter correlação com a síndrome X. Vários estudos têm demonstrado que pacientes com síndrome X e hiper-resistência coronariana (angina microvascular) apresentam elevada incidência de resistên-cia à insulina [28][29][30] , o que talvez faça parte de um distúrbio vascular generalizado envolvendo, até mesmo, as artérias coronarianas.…”
Section: Dor Torácica Não-cardiogênicaunclassified
“…Não apenas diabetes melito, mas, também, seu estado precursor, a resistência à insulina, têm estreita correlação com síndrome X, pois podem desenvolver disfunção microvascular relacionada ao endotélio e à musculatura lisa [28][29][30] . Pacientes com síndrome X, especialmente aqueles com angina microvascular (hiper-resistência coronariana comprovada), apresentam hiperinsulinemias de jejum e durante teste oral de tolerância à glicose.…”
Section: Resistência à Insulinaunclassified